Modern Miracles: Sathya Sai Baba. The Story of a Modern Day Prophet by Erlendur Haraldsson - Roney-Dougal, Serena (Journal of Scientific Exploration, 2014)
This is a revised edition of a book first published in 1987, and most of the material is the same as in the first edition. It comprises a short account of personal interviews with Sathya Sai Baba by the author and various colleagues, as well as extensive interviews with people who were devotees of and close to Sai Baba during the 1940s and 1950s, when his miracles were most prominent. Most of the material is probably beyond most Westerners’ boggle-threshold, which makes an evaluation of it rather tricky. Haraldsson, in his summing-up, clearly considers that the vast majority of the reported materializations for which Sai Baba is most famed are probably genuine. However, he met the man and the interviewees, and therefore probably has greater trust in what they have to say than will the reader who has not met Sai Baba or the interviewees, and maybe has never been to India and so has no idea of the norms of belief within that culture. While I have a measure of sympathy with Haraldsson’s conclusions, I suspect that most Western academics would not. Sathya Sai Baba was born Ratnakaram Sathyanarayana Raju into a low-caste family in 1929 in a remote village some 200 miles from Bangalore in South India. Like most villagers at that time, he had only a rudimentary education and left school after his crisis in 1943, when he was 14 years old. This crisis was ostensibly caused by a bite from a scorpion, which left him unconscious for several hours, and is typical of a shamanic crisis experience. When he recovered he was no longer an ordinary village boy, but claimed to be the reincarnation of a previous south Indian saint known as Shirdi Sai Baba. Hence his name of Sathya Sai Baba. He would frequently fall into trance during the next two decades, so often that he was taken to see a doctor. Some people might see this as a form of possession, especially since those close to him often described him as two very different people—the partially educated village boy who was “very human,” and the divine saint who could do miracles with a flick of his wrist. It took decades for the local villagers to accept Sai Baba as a guru.